Molecular and histopathologic investigation of Pestivirus, Chlamydophila abortus and Listeria monocytogenes infections in aborted sheep foetuses - Kanat, Özgür (Journal of the Hellenic Veterinary Medical Society, 2022)
The aims of this study was to investigate the presence of pestiviruses, Chlamydophila abortus (C. abortus) and Listeria monocytogenes (L. monocytogenes) and histopathological findings caused by these agents in aborted sheep foetuses. A total of 52 aborted sheep foetuses, aged between 1 to 5 months of gestation, were collected from Konya province in Turkey. Molecular techniques were used for detection pestivirus RNA, C. abortus and L. monocytogenes DNA in investigated samples. Pestivirus RNA was detected in 6 (11.5%) of the 52 aborted sheep foetuses whereas C. abortus DNA was determined in 8 (15.4%) foetuses. However, L. monocytogenes DNA was not detected in investigated samples. The significant histopathological findings were hypomyelination, degeneration and necrosis of neurons in the brain, interstitial pneumonia, mononuclear infiltrations in the liver, hyperemia and proximal tubule degeneration in the cortex of kidney in pestivirus positive samples and multifocal purulent-necrotic foci, diffuse neutrophils and mononuclear infiltrations in the liver and spleen, hyperaemia, bleeding, intramyelinic and perivascular oedema, gliosis, neuronophagia in the brain, hyperemia, proximal tubule degeneration and neutrophil granulocyte infiltration in the cortex of kidney were observed in C. abortus positive samples. The results of the study show that C. abortus and pestivirus infections play an important role in abortion in sheep.